A Scientific Review Of The Study Titled: Constitutional Amendments And The Extent Of Their Subjection To Constitutional Judiciary Oversight: A Comparative Study (Eurasian Journal of Media and Communications, 2026)
This paper provides a critical review of the study titled "Constitutional Amendments and the Extent of their Subjection to Constitutional Judiciary Oversight." While the original research advocates for extending the jurisdiction of the Iraqi Federal Supreme Court to include the review of constitutional amendments—both procedurally and substantively—this review presents a counter- argument grounded in the principle of "exclusive jurisdiction." By analyzing Articles 52 and 93 of the 2005 Iraqi Constitution, this paper demonstrates that the Court’s powers are enumerated and cannot be expanded without explicit constitutional text. The review concludes that subjecting constitutional amendments to judicial scrutiny contradicts the Court's specific mandate, which is strictly limited to existing laws and regulations. Relying on established case law, the paper argues that the "Derived Constituent Power" operates outside the Court's purview. Consequently, assuming such oversight would constitute an ultra vires act and a breach of the separation of powers, as the judiciary cannot appoint itself as a guardian over the amendment process absent a clear constitutional authorization